Tinjauan Literatur Sistematis Praktik Pendinginan Aktif Level Bangunan di Negara Iklim Tropis - Anson Ferdiant Diem; Zuber Angkasa; Wiwin A. Oktaviani (Arsir: Jurnal Arsitektur, 2026)
The objective of this paper is to provide a systematic literature review of published research related to active cooling at the building level, specifically in tropical countries, using carefully selected keywords and strict inclusion and exclusion criteria. A total of 82 relevant papers were identified and analyzed. These studies were retrieved using the keywords “air conditioning” and “tropical” in the Scopus database, limited to the period between 2019 and 2025. This review highlights the critical importance of estimating building energy consumption patterns in order to inform strategic decisions regarding active cooling. The available strategies include optimizing existing active cooling systems, integrating passive cooling methods to improve indoor thermal comfort, or replacing conventional systems with more energy-efficient alternatives. Furthermore, the required energy demand is assessed for potential supply through on-site renewable energy sources, such as solar panels, with the aim of achieving net zero energy buildings. To date, there has been no comprehensive literature review focused on active cooling technologies in tropical regions. This study identifies research gaps that have received limited attention and contributes to the development of sustainable cooling policies, which are becoming increasingly urgent in the face of global environmental challenges.